School of Juridical English - I. G. Fedotova (Vestnik MGIMO-Universiteta)
The Department of English Language № 8 works with students of the Faculty of International Law. The unique school of teaching legal aspects of the English language is one of the most significant achievements of the department. Associate Professor V.F. Nazarov was one of professionals, was at the origin of this school. In 1992 the textbook "The course of the legal interpretation of Anglo-American Commercial Law" was published, which was the result of work of group of specialists in legal translation since early 1970s. The book laid foundation for the further development of the school of teaching legal aspects of the English language. After1990stheteaching of the legal aspects of English language was brought to the next level, marked of the by the creation of the educational complex "Legal concepts and categories in the English language" by I.G. Fedotova and G.P. Tolstopyatenko, based on the new competence-based concept of educating professional international lawyers.